The Olive Quick Decline Syndrome: A Syndemic Outbreak in the Apulia Region, Southern Italy - Marco Nuti; Giusto Giovannetti; Marco Scortichini; Giovanni Pergolese; Michele Saracino; Giorgio Doveri (Journal of Agronomy Research, 2021)
Since a decade in Apulia, south-east of Italy, an increasing number of olive trees developed the quick decline syndrome (OQDS) leading to partial or total dessication of the canopy and subsequent death. Currently six million of olive trees show the symptoms of the decline, despite the mitigation measures which were undertaken to contrast the progression of the dessication. Associated with the syndrome, several phytopathogenic fungi were detected in the rhizosphere, endosphere and phyllosphere of the trees, along with the phytopathogenic bacterium Xylellafastidiosasubsp. pauca. Alongside, other pathogenic events were clearly identified, mostly defeating soil resilience: salinization, pollution, erosion, decline of biodiversity. Further events include delays in the adoption of appropriate mitigation measures not directed to challenge solely a bacterial pathogen, misuse of the territory, erratic agronomic management practices. The OQDS impacted also societal aspects. All the above concurrent causes strongly suggest that (1) the olive quick decline in Apulia is not a too symplistic epidemic outbreak due to a bacterium, but rather a syndemic outbreak formed by several diverse biotic and abiotic pathologies and (2) only a more holistic approach can help coping with the uncertainties and difficulties of an enduring co- existance with this syndemic events.
Keywords: syndemic outbreak